In vitro characterisation of ultrasound-induced heating effects in the mother and fetus: A clinical perspective. (May 2021) - Smith, Stephanie F; Miloro, Piero; Axell, Richard; ter Haar, Gail; Lees, Christoph
Introduction: The quantification of heating effects during exposure to ultrasound is usually based on laboratory experiments in water and is assessed using extrapolated parameters such as the thermal index. In our study, we have measured the temperature increase directly in a simulator of the maternal–fetal environment, the 'ISUOG Phantom', using clinically relevant ultrasound scanners, transducers and exposure conditions. Methods: The study was carried out using an instrumented phantom designed to represent the pregnant maternal abdomen and which enabled temperature recordings at positions in tissue mimics which represented the skin surface, sub-surface, amniotic fluid and fetal bone interface. We tested four different transducers on a commercial diagnostic scanner. The effects of scan duration, presence of a circulating fluid, pre-set and power were recorded. Results: The highest temperature increase was always at the transducer–skin interface, where temperature increases between 1.4°C and 9.5°C were observed; lower temperature rises, between 0.1°C and 1.0°C, were observed deeper in tissue and at the bone interface. Doppler modes generated the highest temperature increases. Most of the heating occurred in the first 3 minutes of exposure, with the presence of a circulating fluid having a limited effect. The power setting affected the maximum temperature increase proportionally, with peak temperature increasing from 4.3°C to 6.7°C when power was increased from 63% to 100%. Conclusions: Although this phantom provides a crude mimic of the in vivo conditions, the overall results showed good repeatability and agreement with previously published experiments. All studies showed that the temperature rises observed fell within the recommendations of international regulatory bodies. However, it is important that the operator should be aware of factors affecting the temperature increase.